Influence of protectionist policies on the development of the securities market of China - Lukyanin, Aliaksei D. (Journal of the Belarusian State University. Economics, 2019)
The article identifies the key aspects of the development of the Chinese securities market, the elements of the policy of restriction of the inflow of portfolio investments and the tools of protectionist policies. The impact of protectionist measures on the stock market, price movements, volatility and liquidity has been investigated. It justifies the proposition that stable development can be achieved only in the case of creation of an effective equity capital system with an emphasis on the problem of minority shareholders’ rights.
Keywords: securities market; China; shares; securities; protectionism; portfolio investment